Minyak Atsiri Serai Wangi (Cymbopogon nardus L. Rendle): Diisolasi dengan Dua Metode Berbeda, Kualitas dan Aktivitas Antibakterinya - Afrizal; Defitriani, Anggun; Efdi, Mai (Jurnal Riset Kimia, 2024)
Cymbopogon nardus L. Rendle is one of the world trades essential oil plants. The high selling value of citronella oil is determined by the characteristics of its physical and chemical properties. In this study, determined the physical and chemical properties of citronellal oil isolated by two different methods, namely method of laboratory distillation (M1) and local community distillation (M2). The result showed that the essential oil produce from both methods match with SNI 06-3953-1995 on its physical properties. The results of the chemical composition using Gas Chromatography-Mass Spectrometry (GC-MS) indicated there are 38 and 48 compounds in the essential oil of M1 and M2, respectively with the main compositions are citronellal, citronellol, and geraniol. The antibacterial activity evaluated using the disc diffusion method showed inhibitory ability against the growth of Staphylococcus aureus and Staphylococcus epidermidis, but no inhibitory ability of Pseudomonas aeruginosa. Both, these M1 and M2 essential oils are categorized as a very strong antibacterial at concentration of 3.125% and 50%, respectively.